PERLINDUNGAN HUKUM BAGI RAKYAT AKIBAT TINDAKAN FAKTUAL PEMERINTAH - Bambang Arwanto (Universitas Airlangga, 2016)
The research reveals that The Act No. 30 of 2014 on Government Administration demonstrates the existence of effort to provide a legal protection by requiring the present of clear and legal laws as the base of every government’s acts taken (bestuurs handelingen). This includes providing the chance and way to litigation process for the people who suffer of loss caused by the government’s acts. Especially on the administrative dispute that appears as the result of government’s real act (feitelijke handelingen), transforms its ruling into the Article 85 on the transfer of “onrechmatige overheidsdaad” dispute resolution from the public court into the administrative court, the Article 22 and the Article 29 on the decision/act of discretion, and also the Article 87 letter a on factual act as the expansion element of administrative decision. Consequently, the administrative court has the authority to judge the administrative dispute that appears as the result of government’s real act (feitelijke handelingen) which is only limited to legality testing and not to sue on the basis ofcompensation. It is firmly connected in determining where the legal responsibility lies towards the aggrieved people; whether the compensation becomes the rank responsibility/liability (on the basis of faute de service) or personal responsibility/liability (on the basis of faute de personelle) from the relevant government official.